Block copolymer nanopatterns affect cell spreading: stem versus cancer bone cells - Fontelo, R. (2022)
Bone healing after a tumor removal can be promoted by biomaterials that enhance the bone regeneration and prevent the tumor relapse. Herein, we obtained several nanopatterns by self-assembly of polystyrene-block-poly 2-vinyl pyridine (PS-b-P2VP) with different molecular weight and investigated the adhesion and morphology of human bone marrow mesenchymal stem cells (BMMSC) and osteosarcoma cell line (SaOS-2) on these patterns aiming to identify topography and chemistry that promote bone healing. We analyzed > 2000 cells per experimental condition using imaging software and different morphometric descriptors, namely area, perimeter, aspect ratio, circularity, surface/area, and fractal dimension of cellular contour (FDC). The obtained data were used as inputs for principal component analysis, which showed distinct response of BMMSC and SaOS-2 to the surface topography and chemistry. Among the studied substrates, micellar nanopatterns assembled from the copolymer with high molecular weight promote the adhesion and spreading of BMMSC and have an opposite effect on SaOS-2. This nanopattern is thus beneficial for bone regeneration after injury or pathology, e.g. bone fracture or tumor removal.